Multiple CheY Proteins Control Surface-Associated Lifestyles of Azospirillum brasilense - Ganusova, Elena E.; Vo, Lam T.; Mukherjee, Tanmoy; Alexandre, Gladys (Frontiers in Microbiology, 2021)
Bacterial chemotaxis is the directed movement of motile bacteria in gradients of chemoeffectors. This behavior is mediated by dedicated signal transduction pathways that couple environment sensing with changes in the direction of rotation of flagellar motors, to ultimately affect the motility pattern. Azospirillum brasilense uses two distinct chemotaxis pathways, named Che1 and Che4, and 4 different response regulators (CheY1, CheY4, CheY6 and CheY7) to control the swimming pattern during chemotaxis. Each of the CheY homologs was shown to differentially affect the rotational bias of the polar flagellum and chemotaxis. Here, we characterize the roles of CheY homologs in swimming, swarming as well as attachment to abiotic and biotic (wheat roots) surfaces and biofilm formation. We show that while strains lacking CheY1 and CheY6 are still able to navigate air gradients, strains lacking CheY4 and CheY7 are chemotaxis null. Expansion of swarming colonies in the presence of gradients requires chemotaxis. The induction of swarming depends on CheY4 and CheY7 but organization of cells as dense clusters in productive swarms depends on functional CheYs but not chemotaxis per se. Similarly, functional CheY homologs but not chemotaxis, contribute to attachment to both abiotic and root surfaces as well as to biofilm formation, although these effects are likely dependent on additional cell surface properties such as adhesiveness. Collectively, our data highlight distinct roles for multiple CheY homologs and for chemotaxis during swarming and attachment to surfaces.